Concomitant EGFR mutation and ALK rearrangement in multifocal lung adenocarcinoma: a case report - Jun Fan; Junhua Wu; Bo Huang; Yili Zhu; Heshui Shi; Xiaofang Dai; Xiu Nie (BMC, 2020)
Abstract Background The prevalence of EGFR/ALK co-alterations in patients with NSCLC was low. The several previous studies focused on the simultaneous occurrence of EGFR mutations and ALK rearrangements in a unifocal lung cancer. However, the incidence of multifocal pulmonary adenocarcinomas was increasingly encountered in clinical practice, due to the increased availability and improvement of the thoracic imaging. The clinical relevance of EGFR/ALK co-alterations in multifocal adenocarcinomas required detailed investigation as well. Case presentation We present the case of a 57-year-old woman with solid nodule in the left upper lung and a ground glass nodule in the left lower lobe, who underwent radical operation. Pathological examination confirmed multifocal adenocarcinoma, molecular tests revealed that the left upper lung lesion was positive for ALK rearrangement but the left lower lobe displayed EGFR mutation positive separately. The patient pulmonary lesions were well controlled by adjuvant chemotherapy and radiation therapy. When brain metastases occurred, EGFR-TKI was not effective after firstly administration, while subsequent ALK inhibitors were efficient. We retrospective evaluated the oncogenic status of metastatic lymph nodes and found that the driver gene was ALK rearrangement rather than EGFR mutation. Conclusions The status of the oncogenic mutations in lymph node metastasis may provide some effective hints for metastasis lesion in other organ or tissue. Therefore, it is recommended to fully evaluate the driver genes in lymph node metastasis after radical resection.